CO2 transport: design considerations and project outlook. (November 2015) - Han, Chonghun; Zahid, Umer; An, Jinjoo; Kim, Kyeongsu; Kim, Changsoo
Highlights: The operational range for pipeline and ship transportation of CO2 is quite different. The economical transport option and its operating conditions vary case by case. The concentrations of impurities in CO2 stream should be restricted within allowable range for efficient operation and to ensure safe transport. Regional and global sharing of transport network must be encouraged to reduce transport cost. Abstract : With recent advancements in the carbon capture and storage (CCS), much interest has been developed in the CO2 transport options. In this paper, various aspects associated with the performance and safety of CO2 transportation are reviewed and discussed. The operational range for pipeline and ship transportation of CO2 is quite different, with both methods offering some cons and pros. CO2 stream composition has a great impact on the energy efficiency of the transport chain. In order to facilitate CO2 transportation and reduce its cost, regional and global sharing of transport network must be encouraged. Finally, an up-to-date status on the current and future CO2 transport projects has been presented.